Strategic recommendations for enhancing performance in educational organizations - Tatiana Kokodey; Irina Avdeeva (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
This study examines the performance of "My Horizons", a private K-11 school in Sevastopol that has been facing challenges in achieving satisfactory educational outcomes. The objective of this research is to propose anti-crisis strategic recommendations to improve the effectiveness of the organization. To achieve this goal, the authors have developed a compound methodology that combines qualitative and quantitative econometric methods as a theoretical framework for the study. The first stage of the study involves the formation of an analytical profile of the educational organization. This is accomplished through an analysis and forecast of the main performance indicators, leading to the identification of key features, main characteristics, "problem points," and competitive advantages of the school within the educational services market. In the second stage of the study, based on the results of the analysis and forecast, a set of anti-crisis strategies is formulated for the educational organization. These strategies are specifically designed to address the previously identified "problem points" according to the suggested methodology. By implementing these strategic alternatives, it is expected that the effectiveness of the troubled educational organization will be significantly improved. The findings of this study contribute to the body of knowledge on sustainable educational management practices in crises, explicitlyfocusing on the challenges private schools face. Educational organizations can utilize the proposed methodology to identify areas for improvement and develop effective strategies to overcome crises and enhance performance